Influence of sex and developmental stage on acute hepatotoxic and inflammatory responses to liver procarcinogens in the mouse. (12th December 2016) - Hanna, Daniel; Riedmaier, Ariane Emami; Sugamori, Kim S.; Grant, Denis M.
Abstract: The incidence of liver cancer is higher in men than in women. This sex difference is also observed in murine tumor induction models that result in the appearance of liver tumors in adult mice following their exposure on postnatal days 8 and/or 15 to carcinogens such as 4-aminobiphenyl (ABP) or diethylnitrosamine (DEN). Previous studies performed in adult mice showed that acute hepatotoxic and inflammatory responses to high-dose DEN exposure were greater in males than in females, leading to the suggestion that these responses could account for the sex difference in tumor development. We also recently observed that female but not male mice exposed postnatally to ABP had slightly increased expression of the antioxidant defense genes Nqo1 and Ggt1, which are regulated by the oxidative stress response protein nuclear factor erythroid 2-related factor 2 (NRF2), while expression of Hmox1 was increased in both sexes. The goal of the present study was therefore to compare selected acute hepatotoxic, inflammatory and oxidative stress defense responses to ABP, DEN, or the prototype hepatotoxicant carbon tetrachloride (CCl4 ), in male and female mice exposed to these chemicals either postnatally or as adults. Exposure of adult mice to ABP, DEN or CCl4 produced a 2-fold greater acute elevation in serum levels of the hepatotoxicity biomarker alanine aminotransferase (ALT) in males than in females, while levels of the inflammatory biomarker interleukin-6 (IL-6) showed no sex difference. However, treatment of immature mice with either ABP or DEN using standard tumor-inducing postnatal exposure protocols produced no increase in serum ALT or IL-6 levels in either males or females, while CCl4 produced a 40-fold ALT elevation but with no sex difference. Basal expression of the NRF2-responsive gene Nqo1 was higher in adult females than in males, but there was no sex difference in basal expression of Ggt1 or Hmox1 . Sexually immature animals showed no sex difference in basal expression of any of the three genes. Postnatal DEN exposure modestly increased the expression of Ggt1 only in male mice and Nqo1 in both sexes, while CCl4 slightly increased expression of Ggt1 in both males and females and Nqo1 only in females. Taken together, our results make it unlikely that acute hepatotoxic, inflammatory or NRF2-activated gene responses account for the male predominance in liver tumor growth following postnatal carcinogen exposure in mice. Our findings also suggest that acute toxicity studies performed in adult mice should be interpreted with caution when extrapolating potential mechanisms to liver carcinogenesis models that commonly use postnatally exposed mice.